(3eNJda GdQhGjIs - (3fUQ Hf eMeO Hf CMeO Hf EHQGgje GdSeQbfOj GdMfaj ,CHh GddjK,J (B373 (3g` s ((3CMeO Hf MeRI Hf GdMSf Hf CHh TMeI GdTGei s)
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HPGJg GdeJbOS HCSeGFg hUaGJg hGdUdGI Ydi QShdg GdeDjO HBjGJg heYLRGJg GdeHdZ dCMcGeg hQSdGdGJg hYdi Bdg hGUMGHg hPQjGJg s
(3BNQgG (B:s
(3HGH LhGHGJ eGdc QMeg Gddg bGd TYQ GdejJI WGgQ hYXegG fLS dCf GdTYQ dG MjGI ajg dCfg de jJCde HbWYg HNdGa GdYXe hYfO GdTGaYi cdGgeG fLS hYfOfG cdGgeG WGgQ s
(3GdfSNI HgG MhGTs
(3ai GdNdGajGJ Hjf CHj MfjaI heGdc hGdTGaYis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B91 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B490s
Keywords: (3GNJdGa GdabgGAs